Efecto citotóxico del extracto clorofórmico de las hojas de Annona cherimola en una línea celular de cáncer de pulmón humano en un medio de cultivo con pH ácido - Loján Delgado, Cristian Augusto (2015)
Lung cancer is a malignant tumor that develops from lung and bronchial cells is uncontrolled growth of abnormal cells in the body tissues and organs That damage. Some of These agents, called carcinogenic substances: such as nicotine in snuff act on the body and cause damage to the healthy cell. As a health problem the need Considered For This study was called "Cytotoxic effect of chloroform extract from the leaves of Annona cherimola in a cell line of human lung cancer in a culture medium at acid pH" and Its Intended to verify the cytotoxic activity of the With chloroform extract Annona acid pH leaves Against cherimola lung cancer lines. The study of esta research will be of Experimental Design - Prospective, and the cell line is the A549 lung cancer, the research was Conducted in the city of Loja, in the Laboratory of Biotechnology of the National University of Loja. The techniques used to Identify the cytotoxic effect of the chloroform extract Were cell proliferation and cell viability. It was Concluded That the present research work presents a score of 85.5% cell death With the chloroform extract Which Indicates That Eliminates a lot of cancer cells. Keywords: Lung Cancer 549. Chloroform Extrac